Formation of Physical Culture - Hayitov Tursun Shomurodovich (Genius Publishing Group, 2022)
Physical education, physical culture is a specialized branch of pedagogical science. Physical education (physical training) is a set of activities aimed at developing the morphological and functional abilities of young organisms through exercise. Physical culture, on the other hand, is part of the general culture and is the sum of the achievements of society in the creation and use of special means of human health and physical maturity. Physical education grows into a physical culture and forms a social pedagogical process in society. However, despite the fact that physical education classes in educational institutions (kindergartens, schools, lyceums, vocational schools, higher education) have been held continuously for 14 years, the number of people engaged in physical culture exercises is unsatisfactory. It is only 19-28% of the total population. Modern automated development is comprehensively limiting the physical activity of people, and as a result, the incidence of dangerous diseases in the body is increasing. Physical culture is one of the most effective measures in their timely elimination
Keywords: Physical culture; automated society; inactivity; content